A tandem cell for nanopore-based DNA sequencing with exonuclease. Issue 1 (1st December 2014) - Sampath, G.
Abstract : An electrolytic cell with two nanopores in tandem and an exonuclease in between can efficiently and accurately sequence a single strand of DNA. Abstract : A tandem electrolytic cell with the structure [ cis 1, upstream nanopore (UNP), trans 1 = cis 2, downstream nanopore (DNP), trans 2], an exonuclease enzyme attached to the downstream side of UNP, and a chemical adapter in or a profiled voltage over DNP can be used with bandwidths of a few kHz to sequence bases in ssDNA in natural order with high accuracy and without loss in trans 1/ cis 2 or regression into DNP from trans 2.